Penerapan Metode SMART dalam Sistem Pendukung Keputusan untuk Menilai Kinerja Karyawan - Abdurrahman, M Aulia; Pratama, Dicky (Universitas Multi Data Palembang, 2025)
PT CITRA ANUGERAH LESTARI is a company engaged in General Supplier and Contractor services that serves the National Electricity Company, specializing in the procurement of goods and services. Established in 2014, the company employs 26 people with a permanent employee system in each division of the company. Once a year, PT CITRA ANUGERAH LESTARI conducts a process to determine the best employee based on predefined criteria. However, PT CITRA ANUGERAH LESTARI faces challenges in determining the best employee, which affects the assessment and time efficiency in the selection process. Therefore, a decision support system was developed for PT CITRA ANUGERAH LESTARI using the SMART method. The development method used in creating this system is the Rational Unified Process (RUP) method, while the system design uses Visual Studio Code, MySQL, and Laravel as the framework with PHP programming language. The final result is the determination of the best employee at PT CITRA ANUGERAH LESTARI.